2023
DOI: 10.1002/jia2.26109
|View full text |Cite
|
Sign up to set email alerts
|

Population‐level impact of expanding PrEP coverage by offering long‐acting injectable PrEP to MSM in three high‐resource settings: a model comparison analysis

Abstract: Introduction: Long-acting injectable cabotegravir (CAB-LA) demonstrated superiority to daily tenofovir disoproxil fumarate/emtricitabine (TDF/FTC) for HIV pre-exposure prophylaxis (PrEP) in the HPTN 083/084 trials. We compared the potential impact of expanding PrEP coverage by offering CAB-LA to men who have sex with men (MSM) in Atlanta (US), Montreal (Canada) and the Netherlands, settings with different HIV epidemics. Methods: Three risk-stratified HIV transmission models were independently parameterized and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…1,2 Modeling studies have suggested that among communities with elevated HIV burden, uptake of and adherence to LAI PrEP could expand PrEP utilization, reduce HIV incidence at the community level, and contribute to Ending the HIV Epidemic efforts in the United States (US). [3][4][5] Transgender women-particularly Black and Latina/x transgender women-experience among the highest HIV incidence rates across priority populations within the US HIV epidemic. [6][7][8] Engagement with daily, oral PrEP among transgender women in the United States has been suboptimal, with sociostructural barriers, stigma, and difficulty taking pills associated with lower adherence to a daily, oral regimen.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Modeling studies have suggested that among communities with elevated HIV burden, uptake of and adherence to LAI PrEP could expand PrEP utilization, reduce HIV incidence at the community level, and contribute to Ending the HIV Epidemic efforts in the United States (US). [3][4][5] Transgender women-particularly Black and Latina/x transgender women-experience among the highest HIV incidence rates across priority populations within the US HIV epidemic. [6][7][8] Engagement with daily, oral PrEP among transgender women in the United States has been suboptimal, with sociostructural barriers, stigma, and difficulty taking pills associated with lower adherence to a daily, oral regimen.…”
Section: Introductionmentioning
confidence: 99%
“…These considerations must also align with a country's HIV epidemiologic profile. Stansfield et al.’s [17] research article highlights how high PrEP coverage with CAB‐LA might substantially reduce HIV in settings that experience high HIV incidence. However, the paper also serves as a reminder that LAED regimens may not be a silver bullet and that careful consideration of the epidemiological context is essential as part of the introduction and scaling of LAED regimens.…”
mentioning
confidence: 99%